1992
DOI: 10.1152/jappl.1992.73.6.2517
|View full text |Cite
|
Sign up to set email alerts
|

Training can improve muscle strength and endurance in 78- to 84-yr-old men

Abstract: Nine men, 78-84 yr of age, participated in a dynamometer training program 2-3 times/wk, totaling 25 sessions, using voluntary maximal isometric, concentric, and eccentric right knee-extension actions (30 and 180 degrees/s). Measurements of muscle strength with a Kin-Com dynamometer and simultaneous electromyograms (EMG) were performed of both sides before and after the training period. Muscle biopsies were taken from the right vastus lateralis muscle. The total quadriceps cross-sectional area was measured with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

24
69
1
6

Year Published

1997
1997
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(100 citation statements)
references
References 0 publications
24
69
1
6
Order By: Relevance
“…This is in agreement with previous studies in young (1) and old individuals (27), although not consistently shown (17,31). Furthermore, the pronounced increase in type II fiber CSA seen with RT compensated for the preoperative difference in type I and II fiber CSA (II Ͻ I), which disappeared following RT.…”
Section: Discussionsupporting
confidence: 92%
“…This is in agreement with previous studies in young (1) and old individuals (27), although not consistently shown (17,31). Furthermore, the pronounced increase in type II fiber CSA seen with RT compensated for the preoperative difference in type I and II fiber CSA (II Ͻ I), which disappeared following RT.…”
Section: Discussionsupporting
confidence: 92%
“…Muscular strength improvement was evidenced in upper and lower body strength. Previous studies have showed similar results combining different modes of exercise, with great results increasing both upper-and lower-limb muscular strength (21,22). In addition, our data is consistent with results of another study that showed benefits of square-stepping exercise with respect to improve muscular strength of lower extremely in the older adults (10)(11)(12).…”
Section: Discussionsupporting
confidence: 91%
“…While resistance exercise is a widely used strategy to counteract the age-related loss in muscle mass and strength (Brown et al, 1990;Frontera et al, 1988;Leenders et al, 2013), the hypertrophic response to resistance training or overload may be blunted in old humans (Grimby et al, 1992;Kosek et al, 2006;Martel et al, 2006;Raue et al, 2009;Slivka et al, 2008) and rodents (Alway et al, 2002b;Blough and Linderman, 2000;Degens and Alway, 2003). It has been postulated that the age-related blunted hypertrophy is largely due to a decrease in the number of functional myofibers (Degens, 2012), but a reduced ability of old myofibers to hypertrophy may also contribute.…”
Section: Introductionmentioning
confidence: 99%